A survey on the model-centered approaches to conceptual modeling of IoT systems - Kohan, Sofia; Johnstone, Liam; Cetinkaya, Deniz (Frontiers in Computer Science, 2023)
Internet of Things (IoT) is a system of connected objects, entities, devices and components which share and transfer data over a network. Many papers are published on the topic of conceptual models in the IoT context, but it is difficult to assess the current status of the conceptual modelling approaches and methods for IoT systems. This paper presents an overview of the state of the art as well as discusses fundamental concepts, challenges and current research gaps with potential future agenda for conceptual modelling of IoT. Search facilities in the selected online repositories were used to identify the most relevant papers. The primary results were scanned and papers were selected according to the inclusion/exclusion criteria. Selected papers were assessed to extract data for the defined attributes. This paper confirms that there is a large body of research related to modelling of IoT systems. However, the results show that there is a lack of commonly agreed approaches and supporting formal methods for conceptual modelling of IoT systems. On the other hand, recent studies that apply model-based or model-driven development principles that use ontology or metamodel based approaches are promising due to systematic use of models as the primary means of a development process enabling for the dissemination of the methods further to the emerging fields such as smart cities, factories, transportation, hospitals, healthcare, hospitality and tourism, etc.